Morfologi Bunga dan Korelasinya terhadap Kemampuan Menyerbuk Silang Galur Mandul Jantan Padi - Rumanti, Indrastuti A.; Purwoko, B. S.; Dewi, Iswari S.; Aswidinnoor, Hajrial; Satoto, Satoto (Jurnal Penelitian Pertanian Tanaman Pangan, 2014)
Good male sterile lines should have high and stable sterility, as well as have good characters of flowers that enhances the outcrossing ability. Research was conducted at Sukamandi field station during DS of 2010 to study the character and flowering behaviour and their genetic variability among the new CMS lines. Five new CMS lines were tested in the field in three replicates of randomized complete block design. The results showed that CMS derived from the Wild Abortive, Kalinga and Gambiaca all were early flowering. The new CMS lines have better flower characters than that of IR58025A, including the following: bigger stigma, higher stigma exsertion percentage, wider degree of glume opening, and longer duration of glume opening. Better flowering behaviour enhanced the ability of outcrossing, and resulted in seed set obtained from CMS lines, up to 25.90%; the traditional IR58025A CMS line produced seed set of only 2.98%. The significant positive correlation was found between seed set with stigma width (r = 0.44*), with stigma exsertion (r = 0.54*); and with degree of glume opening of male sterile lines (r = 0.42*); also with filament length (r = 0.47*) and degree of glume opening of maintainer line (r = 0.57**). Those characters are important for the seed set of CMS lines in the hybrid seed production.